Onen Fua Tulu’: a study on the presence of pre-Christian cultural elements in Christian congregation early harvesting services on Timor island - Timo, Ebenhaizer I Nuban (Culture and religion, 2024)
This research describes the presence of pre-Christian cultural elements in harvesting thanksgiving services in Christian congregations on Timor Island as well as analyses the efforts of congregations and church assemblies to transform incorporate the indigenous Pen Suf Bie rite into pre-Christian services directed towards praising spirits to become a thanksgiving service and show of gratitude towards God. There are five pre-Christian cultural elements utilised in an early harvesting thanksgiving service in Christianity: the timing of the service corresponds to the pre-Christian early harvesting time; the service represents a time for family meetings, brotherhood, and joy; praying is effected while kneeling in a rhythmic and poetic language; the pulpit appears to assume the indigenous function of altar; and a communal meal take place at the end of the service. A qualitative method is used with data retrieving techniques in the form of observations, in-depth interviews, focus group discussions, and literature studies. It is argued that church assemblies operate a transformation typology in addressing the relationship between Christ and the culture, which constitute the five typologies introduced by Richard Niebuhr.